2021
DOI: 10.1016/j.csbj.2021.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Towards multi-label classification: Next step of machine learning for microbiome research

Abstract: Machine learning (ML) has been widely used in microbiome research for biomarker selection and disease prediction. By training microbial profiles of samples from patients and healthy controls, ML classifiers constructs data models by community features that highly correlated with the target diseases, so as to determine the status of new samples. To clearly understand the host-microbe interaction of specific diseases, previous studies always focused on well-designed cohorts, in which each sample was exactly labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…output can be directly and seamlessly taken by our previously developed tools like Microbiome Search Engine [35] or Meta-Apo [36], which greatly promotes the data-driven science [37] in this field.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…output can be directly and seamlessly taken by our previously developed tools like Microbiome Search Engine [35] or Meta-Apo [36], which greatly promotes the data-driven science [37] in this field.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The microbiome plays important roles in various fields such as environment protection ( 1 ), bioenergy ( 2 ), food ( 3 ), and human health ( 4 , 5 ). In the past decade, amplicon sequencing of the 16S rRNA gene has been regarded as a fast and low-cost approach to studying the microbiome composition and diversity; hence, it has been employed in numerous works such as the Human Microbiome Project (HMP) ( 6 8 ), Earth Microbiome Project (EMP) ( 9 ), and Metagenomics of the Human Intestinal Tract (MetaHIT) ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study has shown that gut microbiomes with comorbidities can have distinct microbial patterns from those with a single disease, even though they share common biomarkers. [ 9 ] As a result, comorbidities can significantly disrupt disease detection.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study has shown that gut microbiomes with comorbidities can have distinct microbial patterns from those with a single disease, even though they share common biomarkers. [9] As a result, comorbidities can significantly disrupt disease detection. On the other hand, the lifestyle and physiological variables of human hosts have strong connections to various diseases, which can also interfere with the recognition of microbiome-based status.…”
mentioning
confidence: 99%